Pengaruh Pengungkapan Anti Korupsi, Karakteristik Perusahaan Terhadap Profitabilitas Perusahaan: Studi Empiris pada Perusahaaan Perbankan Terdaftar di BEI Periode 2022-2023 - Fransisca Ardieta Amabel Christy; Amelia Setiawan; Hamfri Djajadikerta (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the effect of anti-corruption disclosure and company characteristics on profitability in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2022 period. Profitability is measured using Return on Assets. Anti -corruption disclosure is measured using the ACDI index. Meanwhile, the characteristics of the company are analyzed using several sizes namely, company size, leverage and net profit margin. This study uses a quantitative approach with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis method using the SmartPLS application. The background of this research is based on the high level of corruption cases in the banking sector in Indonesia and the demands of public transparency and accountability for banking companies. The results of this study indicate that anti -corruption disclosure has a positive and significant effect on company profitability. In addition, company characteristics such as size and net profit margin also have a significant effect on profitability. Meanwhile, leverage does not have an effect on profitability. These findings strengthen the importance of implementing anti -corruption policies and management of the company's internal characteristics in improving banking financial performance. The implications of this research are expected to be a consideration for the management of banking companies and regulators in formulating policies that can encourage banking sector companies in Indonesia to implement transparency and good governance.